Polymer Optical Waveguide Grating-Based Biosensor to Detect Effective Drug Concentrations of Ginkgolide A for Inhibition of PMVEC Apoptosis - Chunxue Wang; Pengfei Yi; Jiang Li; Haibing Dong; Changming Chen; Daming Zhang; Haiqing Shen; Bendong Fu (Biosensors, 2021)
In this work, we successfully developed a fluorinated cross-linked polymer Bragg waveguide grating-based optical biosensor to detect effective drug concentrations of ginkgolide A for the inhibition of pulmonary microvascular endothelial cell (PMVEC) apoptosis. Fluorinated photosensitive polymer SU-8 (FSU-8) as the sensing core layer and polymethyl methacrylate (PMMA) as the sensing window cladding were synthesized. The effective drug concentration range (5–10 µg/mL) of ginkgolide A for inhibition of PMVEC apoptosis was analyzed and obtained by pharmacological studies. The structure of the device was optimized to be designed and fabricated by direct UV writing technology. The properties of the biosensor were simulated with various refractive indices of different drug concentrations. The actual sensitivity of the biosensor was measured as 1606.2 nm/RIU. The resolution and detection limit were characterized as 0.05 nm and 3 × 10−5 RIU, respectively. The technique is suitable for safe and accurate detection of effective organic drug dosages of Chinese herbal ingredients.